Transplant and Mongrels and the Law: the Nigeria Experiment - Okunniga, A.A.O. (Obafemi Awolowo University Press, 2012)
The words "transplant" and "mongrels" as used in this lecture are not technical words (or legal words) and they are used here only by way of analogy. Analogy is so frequent in law that it could be said that it is a tool in the "mouth" or the pen of the lawyer. Both words are taken from the biological sciences. The legal transplant then is a statute, or a doctrine, or principle or rule of law taken from one legal order to another legal order e.g. the common law of England was statutorily planted in Nigeria at the beginning of the colonial era, the 'reception date' being 1st January 1900. This is the general pattern in the third-world countries that came under the Suzerainty of Britain. The common law in the United States of America on the other hand cannot properly be regarded as a transplant as the American colonies in fact brought with them the law of their homeland in Britain. The law of the American colonies was really like British law on board a British Ship on British waters. The typical ‘transplant’ moves from home to a foreign land. The Mongrel, on the other hand, is a law or statute or any legal principle or rule derived from more than one origin e.g. it may be partly foreign and partly local. It may also derive from two or more local laws. A law can also be a transplant and a mongrel at the time. Our current Constitution affords a good example of this. The frame-work is that of the United States of America while the fleshing-up is Nigerian.